Polacy w Legii Cudzoziemskiej, 1831-1879 - Bielecki, Robert (Warszawa : PWN, 1992)
A history of the Polish members of the French Foreign Legion, from 1831 to 1879. There is an alphabetical list of names with short biographies.
Polish and French.
At head of title: Naczelna Dyrekcja Archiwow Panstwowych.
Keywords: France. -- Armee. -- Legion etrangere -- Biography -- Dictionaries; Polish people -- Foreign countries -- Biography -- Dictionaries